Weather conditions, brood size and hatching order affect Common Swift Apus apus nestlings survival and growth - SICURELLA, BEATRICE CARLOTTA; AMBROSINI, ROBERTO; Caffi, M; Caprioli, M; Rubolini, D; Saino, N (Bird Study, 2015)
Capsule Hatching order negatively affected Common Swift Apus apus nestlings survival, while brood size and meteorological conditions influenced their growth patterns. Aims To investigate the influence of hatching date, age, sex, brood size and meteorological conditions on survival and growth of Common Swift nestlings from Northern Italy (Southern Europe), a relatively warm and dry part of the distribution range of this species. Methods Nestlings were weighed at regular intervals and molecularly sexed. Growth patterns were described using a double-Richards growth curve, i.e. a growth curve that also accounted for the pre-fledging mass loss. We also identified the Linear Growth Phase (i.e. when nestlings grew at the fastest rate). Results Mortality increased with hatching order and decreased with brood size. Mortality was highest for fourth-hatched nestlings, none of which survived. Nestlings hatched late in the season grew faster, experienced the fastest growth rate at a younger age, but reached a lower maximum weight than nestlings hatched early in the season. Nestlings from large broods reached a lower maximum weight than those of small ones. Nestlings gained more mass when temperature was slightly higher than that expected from the seasonal temperature trend, and on rainy and windy days. Conclusion Common Swift nestlings growth, but not survival, was affected by meteorological conditions, with moderate rainfall, moderate winds and high temperatures favouring greater mass gain. Higher intra-brood competition resulted in slower growth and lower maximum weight. Late-hatched nestlings grew faster but reached a lower maximum weight and a lower pre-fledging mass, possibly suggesting that late-hatched nestlings adaptively tune their growth pattern to the approaching onset of migration to their African wintering quarters. Our results emphasize the importance of exploring weather effects on the breeding biology of a species in different portions of its distribution range that are characterized by contrasting climatic ...